Perbandingan Daya Dukung Tiang Pancang dengan Alat Berat Drop Hammer dan Hydraulic Static Pile Driver (HSPD) - Ardiansyah, Moch. Edwin; Aliehudien, Arief; Gunasti, Amri (Indonesian Journal Publisher, 2024)
The foundation is a base or bottom structure that can carry all the loads above it. Foundation bearing capacity and foundation settlement are very important for foundation planning. In the construction project for the Faculty of Agricultural Technology building at Jember Polytechnic, a recalculation analysis was carried out to compare the carrying capacity using two methods, namely HSPD and Drop Hammer. Soil bearing capacity is calculated based on Standard Penetration Test (SPT) data from 2 soil investigation points. Next, the soil bearing capacity is calculated using the Drop Hammer assumption. The research results show that there is a difference in the carrying capacity of HSPD and Drop Hammer. And the results can be carried out using 2 HSPD heavy equipment and a Drop Hammer at that location. In comparison, Drop Hammer and HSPD driving on a 25 x 25cm mini pile foundation can be carried out. And in the field you can use 2 heavy equipment simultaneously, namely HSPD for spun pile D 50 cm at the smallest permitted carrying capacity value of 68 tonnes at a depth of approximately 12 meters and drop hammer for mini piles at a permitted carrying capacity value of 40.94 tonnes at a depth of approximately 6 meters. However, if you use a drop hammer in areas near residents, don't forget to plan the trench work to reduce vibrations to the surrounding area.